G439(P) Smoking is a paediatric disease: What we can do in secondary care. (24th May 2017) - Beckmann, J; Datt, C; Salkind, J; Robbins, A; Moreiras, J
Abstract : Aims: Smoking cessation is a public health priority, resulting in multiple benefits to individuals as well as health systems. National smoking cessation campaigns have mainly targeted adult, and recently young people groups, but less so families with young children, and little work has been done in secondary care. The aim of our work was to develop smoking cessation training for Paediatric staff and improve smoking cessation pathways for children and young people (CYP) in secondary care. Method: Smoking cessation protocols and staff training were introduced in our Paediatric Department in 2015, Assessment of in-patient outcomes were analysed from casenotes and electronic records at the start and 1 year following these introductions, including recording of smoking history and brief cessation advice, prescription of nicotine-replacement therapy and referral to smoking cessation services. Additionally, a survey was conducted in 2016 to assess staff views on the protocols and available resources. Results: Of 100 cases analysed at each time point, 17%–21% were young people aged 13–18 years. Post-intervention, recording of smoking history in parents and young people had worsened (54% vs 29% in parents and 36% vs 18% in young people), but more parents who smoked were given smoking cessation advice (40% vs 33%). Uptake of nicotine-replacement therapy remained low among the young smokers (40% vs 50%) as were uptake of referrals to smoking cessation services. Staff were supportive of smoking cessation work in Paediatrics, but there were mixed views on the departmental approach and variable levels of awareness of the protocol. Despite the initial intensive training, the lack of improvement over the long-term may be related to staff changes e.g., junior doctor rotation, and limited resources and time for repeated intensive training. Conclusion: Smoking cessation work should remain a priority despite the busy workload in Paediatric departments. However, establishing and sustaining such a service may be more effective with a local champion, e.g., appointment of a smoking cessation CYP support worker. Nonetheless, all Paediatric staff have an essential role in smoking cessation work as part of improving the overall health of children, young people and families.